2007
DOI: 10.4161/auto.3636
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Ageing inC. elegans

Abstract: Previously published online as an Autophagy E-Publication: http://www.landesbioscience.com/journals/autophagy/abstract.php?id=3636 KEy woRdSageing, autophagy, lifespan, atg-7, atg-12, bec-1, daf-2 ACKnowLEdGEmEntS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(164 citation statements)
references
References 17 publications
6
156
0
2
Order By: Relevance
“…RNAi-mediated knockdown of the autophagy regulator bec-1 shortens the lifespan of long-lived daf-2 mutant animals (Kenyon, 2005;Melendez et al, 2003). Moreover, knockdown of the atg-7 and atg-12 C. elegans orthologues shortens the lifespan of both wild-type animals and daf-2 mutants (Hars et al, 2007). Consistent with these findings, loss-of-function mutations in bec-1, atg-18 and lgg-1 abrogate the long-lived phenotype of daf-2 mutants (Toth et al, 2008).…”
Section: Insulin/igf-1 Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAi-mediated knockdown of the autophagy regulator bec-1 shortens the lifespan of long-lived daf-2 mutant animals (Kenyon, 2005;Melendez et al, 2003). Moreover, knockdown of the atg-7 and atg-12 C. elegans orthologues shortens the lifespan of both wild-type animals and daf-2 mutants (Hars et al, 2007). Consistent with these findings, loss-of-function mutations in bec-1, atg-18 and lgg-1 abrogate the long-lived phenotype of daf-2 mutants (Toth et al, 2008).…”
Section: Insulin/igf-1 Signallingmentioning
confidence: 99%
“…Normal dauer larvae are resistant to 1% SDS (Cassada and Russell, 1975). Reduced autophagy results in the formation of abnormal dauer larvae with altered morphology, which lack resistance to SDS and are not long-lived (Hars et al, 2007;Melendez et al, 2003). Knockdown of the autophagy gene bec-1 shortens lifespan of both wild-type and daf-2 mutant worms.…”
Section: Autophagy and Dauer Formation In C Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. elegans, impaired autophagy by knockdown (mutant) of worm bec-1, homologue of yeast VPS30/ mammalian beclin1 [75], as well as atg-7 and atg-12 [76], blocks lifespan extension by a daf-2 mutant. Similarly, lifespan extension via reduced TOR signalling (let-363 aka CeTOR RNAi) has been shown to depend on bec-1, and extension by dietary restriction (eat-2 mutants) has been shown to depend on both bec-1 and vps-34 [77].…”
Section: Introductionmentioning
confidence: 99%
“…Morck and Pilon (2007) demonstrated increased autophagic action as well as smaller cell size in feeding-defective mutants. Hars et al (2007) followed up on studies where RNAi-mediated knock-down of bec-1, a key gene in autophagy, shortened the long life of daf-2 mutants. Here they knocked down two other autophagy genes, atg-7 and atg-12 and showed that RNAi shortened the lifespan of both wild type and daf-2, although not very much.…”
Section: Autophagymentioning
confidence: 99%